Connective Tissue Disease Patients Maintain Greater Distraction During Growth Friendly Surgery. Issue 2 (February 2022) - Marrache, Majd; Suresh, Krishna V.; White, Klane K.; Larson, A. Noelle; Sponseller, Paul D.
Abstract : Study Design: Multicenter retrospective study. Background: Recent studies have demonstrated diminishing returns in patients with early onset scoliosis (EOS) undergoing repeated lengthening of growing rods. Little is known about whether this same phenomenon occurs in patients with lax connective tissue disease (CTD). The primary purpose of this study is to investigate whether EOS patients with connective tissue laxity disorders have diminishing returns during growth friendly surgery. Methods: CTD EOS patients below 10 years old, underwent growth friendly spine surgery with distal anchors and at least 1 proximal spine anchor, and had minimum follow-up of 5 years were included in this study. Coronal T1-S1 height at preindex surgery, postindex, and every available lengthening was assessed. Mean coronal height change during early set distractions and late set distractions were calculated for the cohort. To account for varying distraction intervals, we normalized the distractions by the time interval. The outcome parameter was T1-S1 height gain, mm/year. Results: Twenty-one CTD patients were included in this study. Total coronal height (T1-S1) was 26.7MHCcm before index, 32.2 cm at D1-D3, 34.7 cm at D4-D6, and 36.7 cm at D7-L10. There were no significant differences in coronal height gains between early and late distractions ( P =0.70). Moreover, when normalized for time, there was no significant difference in net gain per year at different lengthening time points for the CTD group, P =0.59. Conclusion: There is no evidence of diminishing returns in coronal T1-S1 height gain in patients with EOS in the setting of CTD. Level of Evidence: Level III.